Trayectos 1 Mi vida en la universidad - Zapata, Gabriela C. (Open textbook library., 2021)
Trayectos is an open curriculum for beginning second language (L2) learners of Spanish. The textbook offers the following features to L2 Spanish students and instructors: Learner-centered fresh, multimodal content, based on Learning by Design, a pedagogy inspired by the Multiliteracies movement (Kalantzis et al., 2005, 2016, 2019; Zapata, 2022). The four modules in Volume I connect the life worlds of learners with the life worlds of diverse Spanish speakers. Instruction incorporating the following features: Multimodal texts (e.g., readings, videos, posters) based on a variety of textual genres that contextualize topics about the lives of real university students; Communicative activities that bind language form to cultural meaning within real-life contexts, and offer students opportunities to discover how to use new Spanish vocabulary and grammar in diverse sociocultural situations; Critical thinking and language awareness tasks that showcase different varieties of Spanish, including those spoken in the United States, and help learners explore the Spanish-speaking world, including local Hispanic/Latinx communities; and Culminating tasks that oblige learners to synthesize their new linguistic and cultural knowledge into a personal, multimodal text. Supplementary digital resources that provide students with opportunities to practice the content learned through self-correcting activities (Práctica individual) and to use Spanish to broaden their knowledge of and critically analyze issues related to diversity, equity, and inclusion in the Spanish-speaking world (Voces de nuestro mundo; available at http://bit.ly/VocesMundo). An open copyright license (Creative Commons license) that gives all users the right to adapt the textbook and to share their new content with others, and digital how-to sections for instructors to answer their students’ unique needs.